Southernmost occurrence of the slender tuna, Allothunnus fallai, off Tierra del Fuego, South Atlantic Ocean - Collette, Bruce B.; Díaz de Astarloa, Juan Martín (Ichthyological Research)
The southernmost record of Allotunnus fallai is here reported Fil: Collette, Bruce B. National Museum of Natural History; Estados Unidos Fil: Díaz de Astarloa, Juan Martín. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina